Renal hybrid oncocytic/chromophobe tumor associated with multiple schwannomas: Case report and literature review. Issue 48 (December 2017) - Liu, Guanghua; Li, Yatong; Li, Zhuoran; Zhou, Jingmin; Huo, Zhen; Ji, Zhigang
Abstract: Rationale: Renal hybrid oncocytic/chromophobe tumors (HOCTs) are benign tumors containing a mixture of cells with features of chromophobe renal cell carcinoma (CHRCC) and renal oncocytoma (RO). Sporadic HOCT, which means HOCT occurs in patients without Birt–Hogg–Dubé syndrome (BHDS) or renal oncocytosis, is extremely rare. In this article, we would report a new case of a patient with both sporadic HOCT and multiple Schwannomas, which is even rarer than simplex sporadic HOCT. Patient concerns: A 48-year-old female was noted with multiple left-kidney masses and a history of multiple Schwannomas. She had no complaints of urological symptoms, abdominal pain, and osphyalgia. The vital sign was stable and blood biochemistry test showed normal renal function. Enhanced computed tomography (CT) found multiple lesions occupying parenchyma of the left kidney. The largest one was measured 3.5 × 3.1 × 3.2 cm. It showed apparently enhancement in arterial phase and low-density in venous phase. Diagnoses: The preoperative diagnosis was renal cell carcinomas. Interventions: The masses were removed by laparoscopic partial left nephrectomy. Outcomes: The diagnosis of HOCT was made by histopathology after surgery. No evidence of local recurrence or distant metastasis was noted on imaging after 2-month follow-up. Lessons: We searched PubMed for cases of sporadic HOCT and a total of 26 patients were evaluated. Our case was the first one involving sporadic HOCT and multiple Schwannomas. Although rare, sporadic HOCT does exist in patients presented with renal mass. Urological surgeons should be aware of the existence of HOCT when considering masses on kidney due to the different prognosis between HOCT and renal cell carcinoma. Further, a possible genetic relationship between HOCT and Schwannoma may contribute to a common pathogenesis in these 2 tumors.